Effect of powder milling and dopant addition on the current-voltage characteristics of SnO2-based ceramics - Lacerda, W. [UNESP]; Las, W. C. [UNESP]; Cilense, M. [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications, 2001)
Non-linear electrical properties of SnO2-based ceramics were investigated as a function of powder agglomeration condition and as a function of dopant addition. All doped powders presented a single phase, cassiterite, as evidenced by X-ray diffraction analysis. The effect of milling was quite evident, with non-milled powder showing higher agglomerated particle size than milled powder. Cr addition seemed to increase the non-linear coefficient. Cu and Mn rendered dense ceramics, but α values for systems with Mn were higher than for systems with Cu.
Keywords: Agglomeration; Annealing; Comminution; Current voltage characteristics; Doping (additives); Particle size analysis; Powders; Tin compounds; X ray diffraction analysis; Dopant; Tin dioxide; Ceramic materials